2023
DOI: 10.3390/app13148557
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparative Study on Permanent-Magnet-Assisted Synchronous Reluctance Motors and Other Types of Motor

Abstract: At present, the induction motor (IM), synchronous reluctance motor (SynRM), ferrite-assisted synchronous reluctance motor (ferrite-assisted SynRM) and interior permanent magnet motor (IPM) are research hotspots, but comprehensive comparative research on the four motors is still rare. This paper mainly compares the four motors from the aspects of electromagnetic performance, material cost and temperature distribution. Firstly, the volume of the four motors is ensured to be the same. The influence of the rotor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This drawback can be overcome, as well as the dimensions of the motor can be reduced by adding inexpensive ferrite magnets to the rotor [14]. Ferrite-assisted SynRMs (FaSynRMs) with high rotor magnetic anisotropy have proven themselves in pumping applications in which a wide CPSR is not required [18][19][20]. Moreover, FaSynRM is also an alternative to IPMSM in electric vehicle applications, with comparable torque capability, lower permanent magnet cost, and better field-weakening capability [21,22].…”
Section: Literature Overview On the Use Of Ferrite-assisted Synchrono...mentioning
confidence: 99%
“…This drawback can be overcome, as well as the dimensions of the motor can be reduced by adding inexpensive ferrite magnets to the rotor [14]. Ferrite-assisted SynRMs (FaSynRMs) with high rotor magnetic anisotropy have proven themselves in pumping applications in which a wide CPSR is not required [18][19][20]. Moreover, FaSynRM is also an alternative to IPMSM in electric vehicle applications, with comparable torque capability, lower permanent magnet cost, and better field-weakening capability [21,22].…”
Section: Literature Overview On the Use Of Ferrite-assisted Synchrono...mentioning
confidence: 99%
“…This motor exhibits numerous advantages, including the absence of rotor windings and permanent magnets, a sturdy rotor construction, no excitation necessity, negligible speed regulation, superior power density, and heightened efficiency [1][2][3][4][5]. Furthermore, its pricing is comparable to that of induction motor drives, making it a competitive option in terms of cost [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Du et al [7] conducted a comprehensive comparative study for four types of electrical machines, i.e., induction motors, synchronous reluctance motors, ferrite-assisted synchronous reluctance motors, and interior permanent magnet motors, regarding electromagnetic performance, material cost, and temperature distribution. It has been found that the electromagnetic performance, heat dissipation, and cost requirements of the four motors are different for different applications.…”
mentioning
confidence: 99%